Spectrophotometric Simultaneous Equation and Area under the Curve Methods for Estimation of Metoprolol Succinate and Telmisartan in Pure Drugs and its Combined Marketed Formulation - Sharma, Vivek; Das, Rina; Mehta, Dinesh Kumar; Chaudhary, Anu; Patel, Samir; Patel, Archita Jayendrakumar (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Telmisartan-metoprolol succinate formulations treat hypertension. The primary goal was to develop and evaluate a UV-spectrophotometric method for estimating telmisartan and metoprolol succinate in a combination tablet dosage form in accordance with ICH standards. Aim: The study aimed to develop a simple, swift, precise, accurate and cost-effective UV spectrophotometric method for the simultaneous estimation of Telmisartan (TEL) and Metoprolol succinate (MET) in a combined tablet dosage form using Hydrochloric acid (HCl) and ethanol as solvents. Materials and Methods: Using HCl (0.1 N) and ethanol as solvents, the approach is predicated on simultaneous equations. MET has an absorbance maximum at 230 nm, while TEL is at 237 nm in its first-order spectrum. For Metoprolol succinate area range is between 229 and 213 nm, while for telmisartan it is between 304 and 277 nm, as determined by the area under the curve method. The reliability, precision, specificity, toughness and robustness of the suggested approach were all verified. Beer's rule was followed by metoprolol succinate and telmisartan between 5-25 μg/mL and 4-20 μg/mL, respectively, with a correlation coefficient value of 0.999. Results: Recovery experiments determined the accuracy of all methods and revealed recoveries between 98-100%. Interday and intraday precision were evaluated and the mean %RSD for all approaches was less than 2%. Conclusion: This study demonstrates that all parameters, including precision, recovery, accuracy and robustness, were met in accordance with ICH guidelines. The analysis's findings have been scientifically and statistically validated.
Keywords: Ethanol; Hydrochloric acid; Metoprolol succinate; Simultaneous equation; Telmisartan; Validation